Seminario WEB: Coherencia en políticas, construcción de paz y sostenibilidad ambiental - Buritica Casanova, Alexander; Castro Nunez, Augusto Carlos (2024)
The webinar aimed to analyze policy coherence in Colombia’s public policies, specifically in the areas of food, water, and land, and to explore how these policies align with the Sustainable Development Goals (SDGs). This event provided a comprehensive perspective from academia and the public sector on policy coherence and its impact on sustainable development.